2001
DOI: 10.1007/s004200100257
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the musk xylene concentrations in plasma samples from the general population from 1992/1993 to 1998 and the relevance of dermal uptake

Abstract: A remarkable decrease in MX levels was found on comparing the values from 1992,1993 and 1998. In 1998 12% (five out of 41) of the samples analyzed yielded positive results for MX (median: <0.1 microg/l, range: <0.1-0.29 microg/l), while in 1993 MX was found in 92% (66 out of 72) of the samples (median: 0.24 microg/l, range: <0.1- 1.12 microg/l). The observed decrease is explained by the discontinued use of MX in detergents in Germany since 1993. As a consequence, no MX could be found in the investigated deterg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A few years later, the concentration of MX was detected to be 0.1 to 1.12 ng/g by Angerer in 1997 [17]. In 1999, Käfferlein [5] reported a remarkable decrease of MX concentration by comparing the values among 1992/1993 and 1998. The change was consistent with the decreased use of MX in European countries.…”
Section: Musk Concentrationsmentioning
confidence: 98%
See 1 more Smart Citation
“…A few years later, the concentration of MX was detected to be 0.1 to 1.12 ng/g by Angerer in 1997 [17]. In 1999, Käfferlein [5] reported a remarkable decrease of MX concentration by comparing the values among 1992/1993 and 1998. The change was consistent with the decreased use of MX in European countries.…”
Section: Musk Concentrationsmentioning
confidence: 98%
“…In the United States it is forbidden to add MX to cosmetic products. In 1993, the German detergent industry voluntarily stopped using MX in their products [4,5]. Now, only a small amount of MK and MX is still used, and it is reported that HHCB, AHTN, MK, and MX represent approximately 95% of the market in Europe for all nitro and polycyclic musk fragrances [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…ADBI and AHMI were only occasionally detected, probably as result of distinctly lower production volumes of these compounds (OSPAR, 2004). That nitro musks were not detected is likely due to their phase out in the 1990s (Käfferlein and Angerer, 2001).…”
Section: Place Figure 2 Herementioning
confidence: 99%
“…Use is still high in the United States, although it is banned in products with a risk of oral uptake (e.g., lipsticks). Toxicologic data have not suggested severe health risks associated with artificial musks, although long-term carcinogenic effects cannot be ruled out (Api et al 2004; Frosch et al 1995; Käfferlein and Angerer 2001; Schmeiser et al 2001); there is also concern about accumulation in adipose tissue, blood plasma, and breast milk (Käfferlein and Angerer 2001; Liebl and Ehrenstorfer 1993; Ott et al 1999; Rimkus and Wolf 1996). …”
mentioning
confidence: 99%